Cognitive-behavioral therapy focused on inhibitory learning, for adults with avoidant/restrictive food intake disorder (ARFID): Study protocol of a prospective study - Malou Masereel; Sebastian Cardona Cano; Trung Dung Tran; Margo de Jonge; Eric Dumont; Annemarie A. van Elburg; Sandra Mulkens (PLoS ONE, 2026)
Objective Currently, there are no evidence-based treatments available for adults with avoidant/restrictive food intake disorder (ARFID). The present paper describes the design of a study evaluating a cognitive-behavioral therapy (CBT) protocol for adults with ARFID, with a focus on exposure using inhibitory learning principles. Method This multicenter study uses a prospective, uncontrolled, repeated-measures design. A total of 120 adults (aged ≥ 18 years) with ARFID will be included via 11 participating treatment centers throughout the Netherlands. Participants will receive a manualized treatment of 25 weekly sessions. Assessments will be conducted at baseline, post-treatment, and at 1- and 12-month follow-ups. The primary outcome is ARFID severity, measured by the Pica, ARFID, and Rumination Disorder Interview (PARDI). Session-level measures of fear and expectancies will be collected throughout the treatment to explore potential mechanisms of change. Treatment effects will be examined across ARFID profiles and comorbid disorders. Discussion This is the first large-scale study to investigate an outpatient CBT program for adults with ARFID. By examining outcomes across ARFID profiles and exploring underlying mechanisms of change, the findings are expected to inform treatment refinement and provide a foundation for future controlled trials. The study has been preregistered in AsPredicted (#212,212) and the trial was registered in the Overview of Medical Research in the Netherlands (NL-OMON6121).